Morocco's Growth and Employment Prospects : Public Policies to Avoid the Middle-Income Trap - Pinto Moreira, Emmanuel (World Bank, Washington, DC, 2019)
This paper studies Morocco's growth and employment prospects in the context of a new growth model aimed at allowing the country, in a rapidly changing international environment marked by increased competition from low-wage economies and growing automation of low-skilled jobs, to avoid falling into a middle-income trap. The first part reviews the growth model that Morocco has pursued in the past few decades and discusses its limitations going forward. The second part characterizes the proposed growth model, which involves, in particular, promoting the transition from labor-intensive imitation activities to technology-intensive innovation activities, increasing public investment in advanced infrastructure, improving the quality of education, improving productivity and increasing value added in key sectors (including agriculture, high-end tourism, and renewable energy), and implementing measures designed to promote women's participation in the labor force and reduce gender inequality. The third part attempts to quantify the medium-run effects of these policies on growth, employment, and unemployment in Morocco. The paper concludes that to achieve high-income status and reduce unemployment significantly, Morocco will need to implement far-reaching reforms, to increase growth to a range of 6-7 percent and improve employment creation to about 35,000 jobs per percentage point of growth.